La violencia intrafamiliar, con maltrato físico a la mujer, en la ciudad de Machala en los años 2008-2009, incidencias socio-jurídicas de las víctimas. Propuesta de reforma al artículo 22 de la ley contra la violencia a la mujer y la familia - Arias Pineda, Walter Alexander (2012)
Domestic violence is a social phenomenon that is present in all societies of the world, without distinction of social classes, where the most affected is women, since many of the time have to silence the abuse suffered, to avoid withstand possible further attacks. The main feature of violence, is the application of the power of the stronger against the weaker and the most visible form of domestic violence is physical or verbal aggression in the case we are dealing with, man aggression against women, children and relatives closest to him.